2003
DOI: 10.1016/s0960-9822(03)00459-7
|View full text |Cite
|
Sign up to set email alerts
|

Elm1p Is One of Three Upstream Kinases for the Saccharomyces cerevisiae SNF1 Complex

Abstract: Elm1p, Pak1p, and Tos3p are upstream kinases for the SNF1 complex that have partially redundant functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
228
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(235 citation statements)
references
References 31 publications
6
228
0
1
Order By: Relevance
“…One of the most studied modes of Snf1 regulation is the phosphorylation of threonine 210, a mark which closely follows Snf1 activation (14,24,36). In this study, we found that in addition to being modified by phosphorylation, Snf1 is modified by ubiquitination.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…One of the most studied modes of Snf1 regulation is the phosphorylation of threonine 210, a mark which closely follows Snf1 activation (14,24,36). In this study, we found that in addition to being modified by phosphorylation, Snf1 is modified by ubiquitination.…”
Section: Discussionmentioning
confidence: 51%
“…Here, we report that Ubp8 can deubiquitinate Snf1, a highly conserved AMP-activated serine/threonine protein kinase that serves as an energy sensor in the cell. Our data indicate that hyperubiquitination of Snf1 affects its stability as well as its phosphorylation status, which is known to affect Snf1 kinase activity (14,24,36). Together, our results suggest that SAGA functions as a master regulator of gene expression not only by altering chromatin structures but also by regulating the stability and activity of transcriptional modulators.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Three upstream kinases, Sak1, Elm1 and Tos3, are responsible for phosphorylation of this threonine residue (Sutherland et al 2003). These kinases appear to be functionally redundant, since only the absence of all three causes a snf1D mutant phenotype.…”
Section: Structure and Regulation Of The Snf1 Kinasementioning
confidence: 99%
“…The SNF1 active protein kinase complex also includes the activating gamma subunit Snf4p (Celenza and Carlson, 1989), and one of three alternate regulatory beta subunits (Sip1p, Sip2p, and Gal83p; Yang et al, 1992Yang et al, , 1994Erickson and Johnston, 1993). Like other protein kinases, SNF1 activity is regulated by upstream kinases, Sak1p (Pak1p), Elm1p and Tos3p (Hong et al, 2003;Sutherland et al, 2003), and protein phosphatases, Reg1p-Glc7p (Sanz et al, 2000). Other levels of regulation include autoinhibition (Leech et al, 2003) and control of its subcellular localization (Hedbacker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%